Perspective Ways of Energy-Efficient Modernization of Heat Supply Systems Based on Heat Pump Technologies - Petrash V.D.; Baryshev V.P.; Shevchenko L.F.; Geraskina E.A.; Danichenko N.V. (Problems of the Regional Energetics)
This work is devoted to determination a generalized indicator for a preliminary assessment of the conditions for increasing the efficiency of modernized systems of centralized and decentral-ized heat supply using heat pump technologies. This goal is achieved through a critical analysis of the results of the actual state of pipelines and equipment, known approaches to the recon-struction of heat supply systems and the establishment of a generalized indicator of the condi-tions for increasing the efficiency of using primary fuel energy. This made it possible to formu-late a generalized approach to the modernization of heat supply systems with the introduction of heat pump technologies. The most important result of the study is the established generalized dependence of the assessment of the increase in the efficiency of heat supply systems on the initial conditions of regime parameters with the rationale for the feasibility of modernizing dis-trict heating systems based on the diverse phased introduction of heat pump technologies at all stages: generation, transportation, distribution, conversion and controlled consumption of heat by subscriber system. The significance of the obtained research results lies in the fact that the proposed approach to the modernization of centralized and decentralized heat supply systems based on heat pump installations with real conversion factors in the range (3--5) with an increase in the available heat potential is to increase the efficiency and expand the use of heat from pri-mary fuel with its savings of 1-2.7 times.